2021
DOI: 10.1186/s40798-021-00299-6
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of High-Intensity Interval Training in Patients with Intensive Care Unit-Acquired Weakness Syndrome Following Long-Term Invasive Ventilation

Abstract: Background Intensive care unit-acquired weakness syndrome (ICUAWS) can be a consequence of long-term mechanical ventilation. Despite recommendations of early patient mobilisation, little is known about the feasibility, safety and benefit of interval training in early rehabilitation facilities (ERF) after long-term invasive ventilation. Methods and Results We retrospectively analysed two established training protocols of bicycle ergometry in ERF pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…It has been reported that long-term admission in ICU enhance neuromuscular weakness, however no literature proves that on short-term admission especially those who underwent many procedures and was in ICU many times within short period inbetween procedures [1][2][3][4][5]. Our case underwent two surgeries in short time.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It has been reported that long-term admission in ICU enhance neuromuscular weakness, however no literature proves that on short-term admission especially those who underwent many procedures and was in ICU many times within short period inbetween procedures [1][2][3][4][5]. Our case underwent two surgeries in short time.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported in many articles that intensive care unit can acquired weakness in many patients especially those who are critically ill in ICU [1][2][3][4][5]. Many factors can be classified as risk factors, include gender, APACHE score, average medical research council score, number of days of ICU stay and number of days of mechanical ventilation [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence shows that these programs are effective in varying clinical contexts, including home and intensive care units. [27][28][29] Low-volume, high-intensity interval exercise programs, although shorter in overall length, still improve overall function, strength, aerobic capacity, and physiological biomarkers. Overall training time is less than 15 minutes (not including warmup or cool down), and a starting interval time of 30 seconds has been recommended to provide increased flexibility for progression/regression in response to patient needs.…”
Section: Construction Of High-intensity Interval Training Programs: H...mentioning
confidence: 99%
“…Regular exercise is known to not only increase muscle strength, power and functional capacity but also is plausible to regulate immunometabolism 92‐96 . To date, studies investigating the effects of short‐term exercise programmes (3‐7 days) on the improvement of muscle functionality during hospitalization have shown an increase in muscle strength, power and functional capacity 97‐103 …”
Section: Exercise: the Key To Counteract Immunometabolic Disturbances...mentioning
confidence: 99%
“…[92][93][94][95][96] To date, studies investigating the effects of short-term exercise programmes (3-7 days) on the improvement of muscle functionality during hospitalization have shown an increase in muscle strength, power and functional capacity. [97][98][99][100][101][102][103] Mechanic stimuli, such as muscle contraction during exercise, activate both the alpha-adrenergic (α-AR) and beta-adrenergic receptors (β-AR). However, α-AR activation is more prominent in the skeletal muscle, stimulating vasoconstriction of inactive muscles, to drive energetic substrates and increase oxygen supply to active muscle groups.…”
Section: Counteract Immunometabolic Disturbances During Disuse-induce...mentioning
confidence: 99%